2008
DOI: 10.1016/j.ijrobp.2008.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Oxygen Image Hypoxic Fraction Plus Radiation Dose Strongly Correlates With Tumor Cure in FSa Fibrosarcomas

Abstract: Purpose-Tumor hypoxia has long been known to produce resistance to radiation. In this study, electron paramagnetic resonance (EPR) oxygen imaging was investigated for its power to predict the success of tumor control depending on tumor oxygenation level and radiation therapy dose.Methods and Materials-Thirty-four EPR oxygen images were obtained from the legs of C3H mice bearing 0.5 ml FSa fibrosarcomas under both normal (air breathing) and clamped tumor conditions. Under the same conditions as those during whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 34 publications
0
62
0
Order By: Relevance
“…EPR imaging can monitor the effects of radiation and chemoradiation in preclinical tumor models using co-registered MRI and EPR imaging data (80). The curative effect of radiation doses (21.1 to 52 Gy) administered to mice bearing FSa tumors was correlated against several descriptors for pO 2 obtained by EPR imaging.…”
Section: The Clinical Importance Of Assessing Tumor Hypoxiamentioning
confidence: 99%
“…EPR imaging can monitor the effects of radiation and chemoradiation in preclinical tumor models using co-registered MRI and EPR imaging data (80). The curative effect of radiation doses (21.1 to 52 Gy) administered to mice bearing FSa tumors was correlated against several descriptors for pO 2 obtained by EPR imaging.…”
Section: The Clinical Importance Of Assessing Tumor Hypoxiamentioning
confidence: 99%
“…Also, Hou et al established a correlation between the effect of the allosteric hemoglobin modifier, efaproxiral, on tumor oxygenation and response to 4 Gy radiation therapy (28). Finally, Elas et al (29) also found data arguing in favor of EPR oximetry as being a good predictor of tumor cure after radiation therapy in FSa tumors under both normal (air breathing) and clamped tumor conditions.…”
Section: Imaging Endpoints For Radiation Therapymentioning
confidence: 99%
“…of Brussels, have embarked on studies to localize areas for eventual surgical removal or correction of regions that have reduced oxygen tension due to tumors, or as a calibration of oxygen pressures suitable for subsequent radiation therapy that has also been a major thrust in the Univ. of Chicago group as well, who are experts on radiation treatment of tumors and tissue [28,29,42].…”
Section: In-vivo Instrumentation With Human Subjectsmentioning
confidence: 99%